PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS VI SD - Nisa, Ainin Zahratun; Adam, Andi; Jaya, Setiawan Uthama (Universitas Tanjungpura, 2024)
Based on the results of observations that have been carried out through providing initial assessments in natural and social science subjects, it was found that there are still many students who are below the KKM, namely 75. So the research aims to apply a problem-based learning model to improve the learning outcomes of VIA SD class students. Tinggimae Presidential Instruction on natural and social science subjects totaling 30 students. The research used was Classroom Action Research (PTK) which was carried out in two learning cycles. Each cycle consists of two meetings and four learning stages, namely: planning, implementation, observation, and reflection. Data collection techniques include observation and tests. Meanwhile, data analysis techniques include quantitative and qualitative analysis. Based on data analysis, the learning outcomes of class VIA SD Inpres Tinggimae students in the pre-cycle learning completion percentage were 27%. In cycle I carried out two meetings the percentage of learning completeness was 67%, and in cycle II carried out two meetings it increased with learning completeness amounting to 80%. Thus, it can be concluded that using a problem-based learning model can improve the learning outcomes of class VIA SD Inpres Tinggimae students in natural and social science subjects.